2009
DOI: 10.1074/jbc.m109.002691
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Proliferation and Migration by TAK1 via Transcriptional Control of von Hippel-Lindau Tumor Suppressor

Abstract: Skin maintenance and healing after wounding requires complex epithelial-mesenchymal interactions purportedly mediated by growth factors and cytokines. We show here that, for wound healing, transforming growth factor-␤-activated kinase 1 (TAK1) in keratinocytes activates von Hippel-Lindau tumor suppressor expression, which in turn represses the expression of platelet-derived growth factor-B (PDGF-B), integrin ␤1, and integrin ␤5 via inhibition of the Sp1-mediated signaling pathway in the keratinocytes. The redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 42 publications
(45 reference statements)
0
33
1
Order By: Relevance
“…Our previous work has shown that this knockdown is specific and can be rescued by transfection with TAK1 cDNA. 10 The overall epidermal thickness between K CTRL and K TAK1 OTCs was similar, but the suprabasal layer of the K TAK1 epidermis was significantly thinner when compared with K CTRL OTC, as evidenced by immunofluorescence staining for involucrin, a marker of keratinocyte terminal differentiation expressed only in the suprabasal layers of epidermis (Figure 1c). 16 Notably, ROS production was elevated in the K TAK1 -derived epithelia, as revealed by DCF staining (Figure 1c).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Our previous work has shown that this knockdown is specific and can be rescued by transfection with TAK1 cDNA. 10 The overall epidermal thickness between K CTRL and K TAK1 OTCs was similar, but the suprabasal layer of the K TAK1 epidermis was significantly thinner when compared with K CTRL OTC, as evidenced by immunofluorescence staining for involucrin, a marker of keratinocyte terminal differentiation expressed only in the suprabasal layers of epidermis (Figure 1c). 16 Notably, ROS production was elevated in the K TAK1 -derived epithelia, as revealed by DCF staining (Figure 1c).…”
Section: Resultsmentioning
confidence: 94%
“…We have previously provided in vivo evidence that the expression of TAK1 is elevated in skin wound biopsies, which peaks at days 3-7 post-injury. 10 To establish a causal relationship between TAK1 and ROS production profile in wound healing, we stained wound biopsies with the fluorescent dye CM-H2DCFDA (DCF). The staining revealed that the wound epithelia were a major site of ROS production that peaked at 3-7 days post-injury, coincident with elevated expression of TAK1 (Figures 1a and b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations